2020
DOI: 10.1103/physrevlett.124.198003
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Buckling of an Elastic Ring in a Soap Film

Abstract: Dynamic buckling may occur when a load is rapidly applied to, or removed from, an elastic object at rest. In contrast to its static counterpart, dynamic buckling offers a wide range of accessible patterns depending on the parameters of the system and the dynamics of the load. To study these effects, we consider experimentally the dynamics of an elastic ring in a soap film when part of the film is suddenly removed. The resulting change in tension applied to the ring creates a range of interesting patterns that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 31 publications
(48 reference statements)
6
25
1
Order By: Relevance
“…(4) is modified by the ring's curvature κ = 1/a, with a being the ring radius. In a related study [22], quantitative agreement with experiment was found by replacing the force F in Eq. (4) with the compressive force induced by the pressure difference p combined with the ring curvature 1/a (Laplace's law), which gives F = pa.…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…(4) is modified by the ring's curvature κ = 1/a, with a being the ring radius. In a related study [22], quantitative agreement with experiment was found by replacing the force F in Eq. (4) with the compressive force induced by the pressure difference p combined with the ring curvature 1/a (Laplace's law), which gives F = pa.…”
Section: Introductionmentioning
confidence: 54%
“…The experiments described in Ref. [22] demonstrate that a circular elastic ring buckling under surface tension in this way can exhibit a range of modes, with higher modes selected dynamically as the importance of surface tension FIG. 1.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations